The Adaption Green Label on Sustainable Hotel Booking Intention in Indonesia - Debbie Aryani Tribudhi; Aifa Nabila (Penerbit Goodwood, 2026)
Purpose: This study examines the influence of green risk perception, green trust, and environmental awareness on online hotel booking intentions in Indonesia. It also explores whether environmental awareness moderates the relationship between green risk perception and booking intention. Methods: A quantitative approach was applied using a survey distributed via social media platforms. A purposive sampling method targeted respondents who had stayed at eco-friendly hotels at least once in the past year. Data from 180 valid responses were analyzed using Structural Equation Modeling (SEM) with SPSS and AMOS to test validity, reliability, and hypothesis relationships. Results: The findings show that green risk perception has a significant positive effect on green trust, and green trust significantly influences online booking intention. In contrast, green risk perception does not significantly affect booking intention, and environmental awareness does not moderate this relationship. Conclusions: The results indicate that trust in hotels’ environmental commitments is more influential in shaping online booking intentions than risk perception or awareness levels. Other practical factors, such as convenience and ease of access, may play a stronger role in consumer decision-making. Limitations: The study is limited by its non-probability sampling approach and the specific focus on eco-friendly hotels in Indonesia, which restricts the generalizability to broader populations or international contexts. Contributions: This study contributes to the literature on green consumer behavior by clarifying the distinct roles of trust, risk, and awareness in online booking decisions. It provides insights for hotel managers to prioritize transparency and trust-building in sustainability communication strategies.